Auditing: The Examination of Financial Statements (Book) . - Downing, Glenn D.; Zeff, Stephen A. (The Accounting Review, 1965)
Reviews the book "Auditing: The Examination of Financial Statements," by Robert L. Grinaker and Ben B. Barr.